A review of climate change effects on practices for mitigating water quality impacts. Issue 4 (22nd March 2022) - Johnson, Thomas; Butcher, Jonathan; Santell, Stephanie; Schwartz, Sara; Julius, Susan; LeDuc, Stephen
Abstract: Water quality practices are commonly implemented to reduce human impacts on land and water resources. In series or parallel in a landscape, systems of practices can reduce local and downstream pollution delivery. Many practices function via physical, chemical, and biological processes that are dependent on weather and climate. Climate change will alter the function of many such systems, though effects will vary in different hydroclimatic and watershed settings. Reducing the risk of impacts will require risk-based, adaptive planning. Here, we review the literature addressing climate change effects on practices commonly used to mitigate the water quality impacts of urban stormwater, agriculture, and forestry. Information from the general literature review is used to make qualitative inferences about the resilience of different types of practices. We discuss resilience in the context of two factors: the sensitivity of practice function to changes in climatic drivers, and the adaptability, or relative ease with which a practice can be modified as change occurs. While only a first step in addressing a complex topic, our aim is to help communities incorporate consideration of resilience to climate change as an additional factor in decisions about water quality practices to meet long-term goals. HIGHLIGHTS: Many water quality practices function via physical, chemical, and biological processes sensitive to weather and climate. Climate change presents a risk to practice-based investments in water quality protection; more resilient practices can help reduce this risk. Practice resilience can be characterized in terms of sensitivity to changes in weather and climate and ability to modify the practice over time. This review is intended to help communities and water resource managers consider climate resilience when adopting practices to meet water quality goals.